Growth Parameters, Protein Digestibility And Health Status Of Rabbit Oryctolagus Cuniculus Fed With Palatable Leafy Vegetables - Yao Konan Franck; Otchoumou Kraidy Athanase; Wognin Legbe Raïssa Marie Flavienne; Konan Konan Anselme; Niamke Sebastien (European Scientific Journal, ESJ, 2016)
This study focused on using vegetable leaves for rabbit feeding. Rabbit fed with leaves of Abelmoschus esculentus, Corchorus olitorius, Ipomea batatas, Vigna unguiculata, Solanum melongena showed positive growth and high feed intake, while rabbits fed with leaves of Amaranthus hybridus, Hibiscus sabdariffa, Manihot esculenta, Celosia argentea, Myrianthus arboreus, Basella alba, Talinum triangulare, Colocasia esculenta showed low feed intake and weight loss. The digestibility of treatments supplemented with concentrate was better than that of the diet without fodder. Feed intake (157.62 g / day) and average weight (2081.87g) of rabbits fed with leaves of Ipomea batatas, were the highest while average daily gain (24.38 - 27.29 g/day) remained similar. The feed conversion ratio of the control treatment (3.51) was better than those obtained for treatments supplemented with concentrate (5.31 - 5.71). Urea and creatinine values were similar in all groups. Blood glucose (0.94 ± 0.04 g/L) and total protein (68.40 ± 0.14 g/L) of rabbit fed with leaves of Solanum melongena were the highest. Total cholesterol of rabbit fed with leaves of Ipomea batatas and control diet were the highest. The blood triglycerides of rabbit fed with control diet was the highest and differed to other treatments (p < 0.05).